The Indonesian Economy : Entering A New Era (ISEAS, 2011)
Indonesia is one of the few countries that came through the global economic crisis in 2008-09 with positive economic growth. Despite some recorded positive domestic economic performances, Indonesia faces new challenges as its economy keeps growing and the global economy remains uncertain. A new economic development paradigm is needed to overcome old problems (poverty and unemployment, inadequate infrastructure, corruption, a complex regulatory environment, and unequal resource distribution among regions) with global market opportunities. This book provides a new perspective on how Indonesians economic policies should be developed by considering its past and future challenges.-- Firmanzah, Professor of Economics and Dean of Faculty of Economics, University of Indonesia